2022
DOI: 10.7554/elife.76071
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics insights into host-viral response and pathogenesis in Crimean-Congo hemorrhagic fever viruses for novel therapeutic target

Abstract: The pathogenesis and host-viral interactions of the Crimean–Congo hemorrhagic fever orthonairovirus (CCHFV) are convoluted and not well evaluated. Application of the multi-omics system biology approaches, including biological network analysis in elucidating the complex host-viral response, interrogates the viral pathogenesis. The present study aimed to fingerprint the system-level alterations during acute CCHFV-infection and the cellular immune responses during productive CCHFV-replication in vitro. We used sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 71 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…Viral infections hijack the cellular metabolic environment, mostly AAs, CCM, and sugars, for their support and propagation [ 11 , 16 , 17 ]. As the significant systemic alteration of the metabolites was glucose, pyruvate/lactate, and glutamate, next we performed flow cytometry analysis of metabolite transporters, glucose transporter-1 (Glut1), pyruvate and lactate transporter monocarboxylate transporter 1 (MCT-1), and cysteine/glutamate antiporter (xCT) in a cohort of HC ( n = 9) and PWH ART ( n = 27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Viral infections hijack the cellular metabolic environment, mostly AAs, CCM, and sugars, for their support and propagation [ 11 , 16 , 17 ]. As the significant systemic alteration of the metabolites was glucose, pyruvate/lactate, and glutamate, next we performed flow cytometry analysis of metabolite transporters, glucose transporter-1 (Glut1), pyruvate and lactate transporter monocarboxylate transporter 1 (MCT-1), and cysteine/glutamate antiporter (xCT) in a cohort of HC ( n = 9) and PWH ART ( n = 27) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This was in contrast to CCHFV infection, for which we could not detect an impact of core autophagy gene engagement on virion production. Whether the marked endoplasmic reticulum (ER)-stress response [ 31 ] and hijacking of carbon and energy metabolism [ 42 ] that were uncovered in CCHFV-infected cells are also taking place in DUGV-infected cells and whether they impact the anti-viral autophagy of epithelial cells remain to be studied. In a comparative analysis of primary human antigen presenting cells (dendritic cells and macrophages derived from blood progenitors), DUGV was found to induce higher levels of cytokine and chemokine production (interleukin-6, RANTES, IP-10, and MIP-1α) than CCHFV, especially in the case of macrophages [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that viruses alter the metabolism of host cells in order to provide optimal conditions for rapid and efficient reproduction and transmission ( 9 12 ). Viruses rely on the host cell machinery for reproduction.…”
Section: Introductionmentioning
confidence: 99%